MYANMAR MILITARY COUP ON 2021 : RESTORE THE GLORY ERA OF OPIUM - Mike Natanael Norend Mandagie (Kajian Asia Pasifik, 2023)
Military coups are nothing new in the 21st century. Myanmar's military overthrew the existing democratic government in a coup d'Ã©tat to gain power. Opium is the key behind the Myanmar military coup taking place in 2021. This article was written using both qualitative and quantitative methodologies. News in the mass media, both print and online, is also a source. The thirst for power has influenced the existing military so that actions without morals are committed. Many people consider that the coup carried out by the Myanmar military was an ordinary coup that was normalized because of the thirst for power. But behind that thirst for power lies a bigger plan for profit. The public needs to see the real reason behind the coup carried out by the Myanmar military in 2021 so that it can clearly and structuredly understand the coup that was carried out in 2021 which further put Aung San Suu Kyi under house arrest Keywords: Opium, Government, Military, Power, Coup